The use of food processing terminology in Australian news media: a content analysis - Cherie Russell; Katherine E Sievert; Sarah Dickie; Priscila Pereira Machado (Cambridge University Press, 2024)
Abstract Objective: This study aims to determine whether ultra-processed foods (UPFs) are being discussed in news media in Australia and whether this terminology, as described in the NOVA system, is being applied accurately. Design: Interpretive content analysis of online and print media articles that mentioned UPFs from 2009 to 2023 in Australia. Setting: Australia. Participants: Online and print media articles. Results: A total of two hundred ninety-eight Australian media articles were captured. A substantial increase in the number of UPF articles was observed between 2017-2019 and 2021-2023. The UPF concept was inaccurately explained or defined in 32 % of the articles and was frequently used interchangeably with other descriptors, such as 'highly or heavily processed food', 'junk food', 'unhealthy food', 'packaged food' and 'discretionary food'. Most of the articles had a health focus; however, sustainability interest increased, particularly in the past 18 months. Conclusions: UPFs are increasingly being discussed in news media in Australia; however, the concept is still incorrectly presented in over a third of articles. This highlights the importance of improving the literacy about UPFs to ensure that messages are communicated in a way that is salient, accessible and accurate.